2011
DOI: 10.1001/archgenpsychiatry.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Early Brain Overgrowth in Autism Associated With an Increase in Cortical Surface Area Before Age 2 Years

Abstract: Objective Brain enlargement has been observed in 2 year old children with autism but the underlying mechanisms are unknown. This longitudinal MRI study investigated early growth trajectories in brain volume and cortical thickness. Method Cerebral gray and white matter volumes and cortical thickness in children with autism spectrum disorder and controls were examined. Subjects were seen at approximately 2 years of age (autism = 59, controls = 38) and were rescanned approximately 24 months later at age 4–5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
351
4
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(408 citation statements)
references
References 54 publications
(88 reference statements)
34
351
4
19
Order By: Relevance
“…Structural brain imaging studies examining cerebral morphology in individuals with autism have provided somehow inconsistent results to date. One of the most replicated finding is the cerebral enlargement observed in children aged 2-4 years old [83,84]. The study examining the largest sample to date (n = 586) [85] indeed observed that cerebral volumes are increased up to the age of 7, but decreased thereafter in older children, adolescents and adults with autism.…”
Section: Neuroimaging Studiesmentioning
confidence: 95%
“…Structural brain imaging studies examining cerebral morphology in individuals with autism have provided somehow inconsistent results to date. One of the most replicated finding is the cerebral enlargement observed in children aged 2-4 years old [83,84]. The study examining the largest sample to date (n = 586) [85] indeed observed that cerebral volumes are increased up to the age of 7, but decreased thereafter in older children, adolescents and adults with autism.…”
Section: Neuroimaging Studiesmentioning
confidence: 95%
“…Examples include deciding whether providing drug treatment to inmates reduces recidivism, testing the effectiveness of medical treatments, and the Atlanta standardized test cheating scandal of 2009. Several pages are devoted to a 2011 study in the Archives of General Psychiatry (Hazlett et al 2011) on autism spectrum disorder, and how a study that includes only 97 subjects can actually produce results we can be statistically confident of.…”
Section: The Bookmentioning
confidence: 99%
“…Development peaks occur between 2 and 5 years of age, when cranial circumferences are above average and cerebral volume increases, and are followed, in adolescent and adult ages, by reduced cerebral dimension and function (Aylward et al, 2002;Courchesne et al, 2010;Hazlett et al, 2011). The evaluation and monitoring of child development dynamics may be performed using WHO Anthro software (World Health Organization-WHO, 2011), made in accordance with WHO standards (WHO, 2007) for children aged between 0 and 5.…”
Section: Wwwintechopencommentioning
confidence: 99%